2012
DOI: 10.1007/s10147-012-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free human telomerase reverse transcriptase mRNA in plasma and its potential diagnostic and prognostic value for gastric cancer

Abstract: We concluded that circulating cell-free hTERT mRNA might serve as a potential and useful noninvasive tumor marker for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…18,27,37 In the present study, rigorous efforts to eliminate DNA from samples of RNA, as well as limiting the number of cycles for amplification of hTERT cDNA to prevent false-positive results, might have contributed to diminished sensitivity. 18,27,37 In the present study, rigorous efforts to eliminate DNA from samples of RNA, as well as limiting the number of cycles for amplification of hTERT cDNA to prevent false-positive results, might have contributed to diminished sensitivity.…”
Section: Discussionmentioning
confidence: 94%
“…18,27,37 In the present study, rigorous efforts to eliminate DNA from samples of RNA, as well as limiting the number of cycles for amplification of hTERT cDNA to prevent false-positive results, might have contributed to diminished sensitivity. 18,27,37 In the present study, rigorous efforts to eliminate DNA from samples of RNA, as well as limiting the number of cycles for amplification of hTERT cDNA to prevent false-positive results, might have contributed to diminished sensitivity.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the elevated concentration of circulating RNA has been shown to be closely associated with poor prognosis in esophageal cancer, breast cancer or lymphoma 17-19. The increase of circulating cell-free hTERT mRNA was demonstrated to be correlated with reduced disease-free survival and overall survival in gastric cancer patients by Kang et al 20. As to plasma mRNA of CML-derived genes, Ma et al have reported that plasma was a reliable source for monitoring BCR-ABL mRNA levels and that minimal residual disease detection from plasma was more sensitive than from cell samples.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be used as a non-invasive marker of prostate cancer to differentiate patients with locally advanced disease at molecular level. Kang [7] and March-Villalba et al [19] detected peripheral hTERT mRNA content in patients with gastric and prostate cancer, respectively. Their results showed that hTERT mRNA content in these cancer patients was higher than that in control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have showed that detection of free RNA in peripheral blood has higher sensitivity and tissue specificity than conventional tumor biomarkers [46], which opens a new field in tumor diagnosis, therapeutic evaluation and prognosis assessment. In recent years, many studies have detected hTERT mRNA in peripheral blood of patients with different tumors such as prostate cancer, lung cancer and stomach cancer [4, 5, 7] and demonstrated that elevated hTERT mRNA in peripheral blood is closely related with clinicopathological parameters, treatment efficacy and other tumor biomarkers of cancer patients.…”
Section: Introductionmentioning
confidence: 99%